Impact of Gamified Training Techniques on Employee Skill Development in Financial Institutions in Germany - Schulz, Tim (Human Resource and Leadership Journal, 2025)
Purpose: The purpose of this article was to impact of gamified training techniques on employee skill development in financial institutions in Germany. Methodology: This study adopted a desk methodology. A desk study research design is commonly known as secondary data collection. This is basically collecting data from existing resources preferably because of its low cost advantage as compared to a field research. Our current study looked into already published studies and reports as the data was easily accessed through online journals and libraries. Findings: ​ Gamified training in German financial institutions has boosted employee engagement, skill retention, and motivation. Game elements like points and challenges made learning more effective and enjoyable. Employees showed better problem-solving and adaptability. The approach modernized training and improved overall performance. Unique Contribution to Theory, Practice and Policy: Self-determination theory (SDT), flow theory & goal-setting theory may be used to anchor future studies on impact of gamified training techniques on employee skill development in financial institutions in Germany. For practitioners, gamified training offers an innovative and scalable method to enhance employee development across diverse financial domains such as risk management, cybersecurity, compliance, and customer service. Government agencies and financial regulators should collaborate with industry stakeholders to create guidelines that encourage the ethical and inclusive use of gamified tools, ensuring accessibility and fairness for all employees.